Diagnosis and treatment of abdominally inserted (sacrocolpopexy/sacrohysteropexy) mesh complications for vault/uterine prolapse - Karen Ward; Eric Bautrant; Gaurav Khatri; Sarah Love-Jones; Phyllis Glanc; Charlotte Korte; Nicolle Germano; Sherif Mourad; Hashim Hashim (Continence)
Background:: Sacrohysteropexy and sacrocolpopexy are established treatments of uterine or vaginal vault prolapse respectively and involve insertion of mesh abdominally, often using permanent sutures and fixation devices. Complications following these procedures may be serious, and there is lack of evidence about long-term functional outcomes in terms of pain, dyspareunia and development of lower urinary tract and bowel symptoms. Objective:: A non-systematic review of the available literature was performed and recommendations on assessment and management were developed by expert consensus. Conclusion:: The current evidence is limited in quantity and quality, and recommendations on assessment management of mesh-related complications were made by experts in the field. Assessment and treatment of complications following abdominally placed mesh for pelvic organ prolapse will often require a multidisciplinary approach. Assessment may require EUA, and/or cystourethroscopy, sigmoidoscopy, and laparoscopy. MRI is the most useful imaging modality. Surgery to remove mesh carries a risk of urinary tract and bowel injury, as well as development of recurrent pelvic organ prolapse. A joint decision between the surgeon and the patient should be made before embarking on a partial removal of mesh; removal of all the mesh may be a better option albeit with higher risk of surgical complications. Complete removal of mesh and tacks or sutures from the sacral attachment may not be possible and is associated with risk of major haemorrhage.